Structure Activity Relationships of 5-, 6-, and 7-Methyl-Substituted Azepan-3-one Cathepsin K Inhibitors - Yamashita, Dennis S; Marquis, Robert W; Xie, Ren; Nidamarthy, Sirishkumar D; Oh, Hye-Ja; Jeong, Jae U; Erhard, Karl F; Ward, Keith W; Roethke, Theresa J; Smith, Brian R; Cheng, H-Y; Geng, Xiaoliu; et al. (Journal of medicinal chemistry, 2006)
The syntheses, in vitro characterizations, and rat and monkey in vivo pharmacokinetic profiles of a series of 5-, 6-, and 7-methyl-substituted azepanone-based cathepsin K inhibitors are described. Depending on the particular regiochemical substitution and stereochemical configuration, methyl-substituted azepanones were identified that had widely varied cathepsin K inhibitory potency as well as pharmacokinetic properties compared to the 4S-parent azepanone analogue, 1 (human cathepsin K, K i,app = 0.16 nM, rat oral bioavailability = 42%, rat in vivo clearance = 49.2 mL/min/kg). Of particular note, the 4S-7-cis-methylazepanone analogue, 10, had a K i,app = 0.041 nM vs human cathepsin K and 89% oral bioavailability and an in vivo clearance rate of 19.5 mL/min/kg in the rat. Hypotheses that rationalize some of the observed characteristics of these closely related analogues have been made using X-ray crystallography and conformational analysis. These examples demonstrate the potential for modulation of pharmacological properties of cathepsin inhibitors by substituting the azepanone core. The high potency for inhibition of cathepsin K coupled with the favorable rat and monkey pharmacokinetic characteristics of compound 10, also known as SB-462795 or relacatib, has made it the subject of considerable in vivo evaluation for safety and efficacy as an inhibitor of excessive bone resorption in rat, monkey, and human studies, which will be reported elsewhere.